Laser‐Triggered Writing and Biofunctionalization of Thiol‐Ene Networks. Issue 10 (16th April 2020) - Romano, Angelo; Angelini, Angelo; Rossegger, Elisabeth; Palmara, Gianluca; Castellino, Micaela; Frascella, Francesca; Chiappone, Annalisa; Chiadò, Alessandro; Sangermano, Marco; Schlögl, Sandra; Roppolo, Ignazio
Abstract: The light responsivity of ortho‐nitrobenzyl esters ( o ‐NBE) is exploited to inscribe µ‐scale 2.5D patterns in thiol‐ene networks by direct laser writing. For this purpose, a multifunctional thiol and a photosensitive alkene with an o ‐NBE chromophore are cured upon visible light exposure without inducing a premature photocleavage of the o ‐NBE links. Once the network is formed, a laser beam source with a wavelength of 375 nm is used for selectively inducing the photocleavage reaction of the o ‐NBE groups. Positive tone patterns are directly inscribed onto the sample surface without the requirement of a subsequent development step (removing soluble species in an appropriate organic solvent). Along with the realization of dry‐developable micropatterns, the chemical surface composition of the exposed areas can be conveniently adjusted since different domains with a tailored content of carboxylic groups are obtained simply by modulating the laser energy dose. In a following step, those are activated and exploited as anchor points for attaching an Alexa‐546 conjugated Protein A. Thus, the laser writable thiol‐ene networks do not only provide a convenient method for the fabrication of positive tone patterns but also open future prospectives for a wide range of biosensing applications. Abstract : Laser writing is used to produce 2.5D patterns in a thiol‐ene photocured coating taking advantage of the photo‐decrosslinking of ortho‐nitrobenzyl ester groups. Furthermore, this technique is used to manipulate the extent of the photocleavage in order to control the amount of carboxylic groups in the patterned domains: these functional groups are exploited for selective protein biofunctionalization.